Investigating the Use of E-learning as Innovative Strategy to Improve Beninese EFL Learners’ Linguistic Performance: Case Study of FLASH Adjarra - DADJO, Servais Dieu-Donné Yédia (My University, 2022)
This paper investigates the use of e-learning as innovative strategy to improve Beninese EFL learners’ linguistic performance : case study of FLASH Adjarra, University of Abomey-Calavi. In other words, the study examines the impacts of eteaching- learning process of English as Foreign Language on learners’ linguistic performance. Through a mixed-method, the data have been collected from questionnaires addressed to both lecturers and Year 1 learners of the English Department of FLASH Adjarra. The results show that e-learning provides opportunities for learners to practise repeatedly listening and speaking activities where and when they want as there is no geographical and spatial barriers for them to learn English. E-learning impacts positively learners’ linguistic performance. Moreover, it is contended that e-learning enables an immediate and a rapid assessment of learners as well as an immediate correction of errors or mistakes. Consequently, e-learning is viewed as an innovative and useful strategy particularly for French speaking country like Benin where learners do not have the opportunity to be exposed to a natural English learning environment. Thus, it is relevant to adopt e-learning especially for EFL learners due to its valuable advantages.
Keywords: e-learning; linguistic performance; listening; speaking skills